Terroryzm islamski - Piąty jeździec apokalipsy - Chudy, Małgorzata (My University, 2015)
Terroryzm islamski ma długą historię, powstał bowiem we wczesnym średniowieczu. Jak dawniej, tak i dzisiaj dla działań gwałtownych, dla posługiwania się przemocą, czyli prowadzenia „świętej wojny" poszukują usprawiedliwienia w nakazach Proroka. W czasach nam współczesnych, kiedy nienawiść świata islamskiego do Zachodu stała się niemal obsesją młodego pokolenia muzułmanów, można zaryzykować twierdzenie, że islam zagraża światu. Ich starsi współwyznawcy zdołali im wpoić absurdalną teorię obciążającą. Większość wyznawców islamu, zwłaszcza z krajów, w których jest on religią dominującą lub państwową łączy jedno -niechętny bądź wręcz wrogi stosunek do cywilizacji Zachodu. Znajduje to potwierdzenie w faktach choćby ostatniego dziesięciolecia. Najbardziej radykalni muzułmanie głoszą potrzebę walki z „zachodnim szatanem", a ponieważ nie są w stanie wystąpić otwarcie i poprowadzić podboje, jak to czynili ich przodkowie, począwszy od VII wieku, więc łączą się w organizacje terrorystyczne. Wszystko wskazuje na to, że islam jest w ofensywie. Zdobywa wpływy na nowych terytoriach, zwłaszcza w Czarnej Afryce.

Terrorism, under the name of Islam, has a long history and was first established in the early Middle- Ages. As in the past and even today, for violent action, use of force and conducting a "holy war", Islamist terrorism is seeking a justification in the Prophet’s teachings. In the present time with hatred from the Islamic world to the West, it has become almost an obsession of some of the younger generation of Muslims; one can dare say that Islam threatens the whole world. Their older fellow believers managed to instil into them an absurd aggravating theory. The majority of Muslims, especially in countries where it is the dominant religion, state they have one thing in common –unwillingness or even hostility to Western civilization. This is confirmed by the facts known for at least in the last decade. The most radical Muslims claim the need to combat "western Satan," but because they are not able to come out openly and lead the conquest as did their ancestors, starting from the seventh century, they combine into terrorist organizations. Everything seems to indicate that Islam is offensive. Islam is also gaining influence in the new territories, particularly in sub-Saharan Africa.
Islamic terrorism - The fifth horseman of the apocalypse
Keywords: Islam; fundamentalizm religijny; współpraca; zagrożenie; religia; religious fundamentalism; cooperation; danger; religion; terroryzm; terrorism